Analyzing thermoelectric transport in n-type Mg2Si0.4Sn0.6 and correlation with microstructural effects: An insight on the role of Mg. (15th October 2020) - Sankhla, Aryan; Kamila, Hasbuna; Kelm, Klemens; Mueller, Eckhard; de Boor, Johannes
Abstract: Fundamental material parameters governing the carrier transport in thermoelectric materials are affected by microstructural characteristics. We have investigated the effects of compaction duration on microstructure and the thermoelectric properties of Sb doped Mg2 Si0.4 Sn0.6 . The transport properties show drastic changes with increasing compaction duration from 10 min to 40 min. A TEM-EDS analysis on samples sintered for 20 min and 40 min highlights Mg depleted grain boundaries and local compositional inhomogeneities but gives no indications for dopant loss. The transport properties were analyzed using a single parabolic band (SPB) model, and the observed changes can be attributed to carrier ( n ) loss, diminished carrier mobility ( μ 0 ) and a reduction in lattice thermal conductivity ( κlat ). Comparatively stronger carrier scattering in longer sintered sample is a combined effect of increasing electron-phonon interaction (higher EDef ) and local compositional inhomogeneities in the material which are both linked to Mg depletion. The transport behavior of these samples can be fully captured by the SPB model only after the addition of grain boundary scattering in conjunction to acoustic phonon and alloy scattering. Furthermore, compensation between a lower κlat and μ 0 of the longer sintered sample led to a similar z T m a x = 1.3 ± 0.18 and an only marginally reduced performance parameter β . While it is evident that Mg deficiency modifies the transport properties, the thermoelectric performance is only mildly affected and a Mg2 (Si, Sn) based TE device can therefore withstand some Mg loss without a deterioration of its performance. Graphical abstract: Image, graphical abstract